PROBLEMS AND PROSPECTS OF RECOVERY OF UKRAINE DURING AND AFTER THE END OF THE RUSSIAN-UKRAINIAN WAR - PANKIV, Natalia; CHERNYSHOVA, Anastasiya (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The work examines the problems and prospects of restoring Ukraine during and after the end of the Russian-Ukrainian war. Because Russia's full-scale invasion of Ukraine, which began more than eight months ago, has resulted in large-scale human casualties, massive population displacement, and significant infrastructure damage. The impact on economic activity was also enormous: real Gross Domestic Product (GDP) fell sharply, inflation soared, trade was severely disrupted, and the budget deficit rose to unprecedented levels. More than 7 million Ukrainians – about a fifth of the population – have left the country or become internally displaced, which puts pressure on the social protection system. The report said that logistical problems related to the war continue to strain the economy, mainly related to the operation of ports, transport networks, and energy infrastructure. The war also caused an imbalance in the foreign exchange market.Therefore, the article analyzes the main events and development of the economy during martial law in the country, identifies problems, and substantiates the optimal conditions for the future development of Ukrainian tourism, which ranks third among all economic sectors in terms of income in the country's economy. The essence and main influence of military operations on the development of international tourism in the world are substantiated. The development of the Russian-Ukrainian war, the main events, and the territorial features of the development are analyzed. The countries that are allies of Ukraine are highlighted, and the international aid and support of world powers that Ukraine receives in 2022 are analyzed.Ukrainian and world tourism during the war is characterized, and their main changes and development trends are revealed. The influence of the Russian-Ukrainian war on the economy of Ukraine and the world is revealed, and the humanitarian consequences of the military conflict for the countries of Europe and Ukraine are also predicted. Already existing plans for the restoration of Ukraine's infrastructure after the end of the war have been analyzed and other possible options for the development of reconstruction have been predicted. The extent to which measures are being prepared to support and restore the tourism industry and the economy and its realism has been established.
Keywords: Russian-Ukrainian war; humanitarian crisis; economic development; tourism; recovery plan of Ukraine